Tropical Pines in Madhya Pradesh - Chaturvedi, J. K. (Indian Forester, 1982)
Tropical Pines in Madhya Pradesh were first introduced in Amarkantak resion in 1968. Number of experiments were conducted at Amarkantak field station under State Forest Research Institute on nursery technique, choice of species, spacement, fertilizer applicatiOn etc. and technique of planting was standardized. Identification of suitable areas for raising tropical Pines in the State was done and small trial plantations were undertaken. Based on the field data of such trials, Madhya Pradesh State Forest Development Corporation submitted a Pine Plantation Project for Bastar which was financed by World Bank from 1-4-76. Tropical Pines have been raised over an area of 230 ha and 1356 ha under research trials and pilot plantations respectively in Bastar. Tentative conclusions have been drawn from a number of experiments. Tests have shown the suitability of tropical Pines for pulpwood. Growth data has confirmed the fast growth of species and its increased outtura per hectare has encouraged the prospects of a paper industry in the region.